Analisis Pengaruh Kualitas Pelayanan, Lokasi Dan Harga Terhadap Kepuasan Nasabah Melalui Keputusan Pembelian Sebagai Variabel Intervening Pada Penjualan Logam Mulia Emas - Hasanuddin, Makmur (Universitas Sam Ratulangi, 2016)
To improve customer satisfaction, the company required the efforts of every management in all outlets PT Pegadaian (Persero) throughout Indonesia to improve service quality. The results showed that the indirect effect of service quality on customer satisfaction through purchasing decisions influence positively and significantly. The direct effect of the location of the customer satisfaction is a positive, but not significant. Indirect effect on location about customer satisfaction through thepurchase decision is negative and insignificant. The direct effect on customer satisfaction rates are positive, but not significant. Indirect influence of price on customer satisfaction through positive and significant purchase decisions. Direct influence on the purchase decision is positive and significant.Keywords: Quality of Service, Location, Price, Customer Satisfaction, Purchase Decision, PreciousMetals Gold